Beyond Medicine: Unveiling Rural-Urban Contrasts in Faith based Healing Practices in Multan, Pakistan - Muhammad Meesum Hassan; Sidra Hussain; Ali Murad; Dr. Saima Afzal (Journal of Peace, Development and Communication, 2024)
The study aimed to identify the prevalence and personal experience of spiritual and ritual healing practices as well as to differentiate the Faith healing practices in Rural and Urban areas and to identify the different types of spiritual curatives being used in Rural and urban areas. The respondents were male and female b/w the age of 18-50 years from Rural and Urban Union Councils of Multan. It followed a Cross-sectional Quantitative research design. A sample of 394 respondents was used, and data were collected using a multi-stage purposive sampling technique. A structured interview schedule was used to collect the data. Using SPSS Cross tabulations and descriptive statistics, such as frequency and percentages, were carried out. Independent sample t test was used to compare belief in Spiritual Healing, belief in Extrinsic Spiritual Curatives and belief in Intrinsic Spiritual Curatives between rural and urban population. Moreover, Correlation was also applied to see the correlation of different variables associated with spiritual healing. Many respondents believed spiritual healing is genuine and efficient. Most respondents thought religious and otherworldly factors caused diseases and afflictions. They accepted that God or supernatural entities are capable of causing illness, and afflictions may be examinations or punishments. Rituals and magic could also cause illness. Many respondents believed in faith healers. The attitudes towards spiritual healing differ noticeably between rural and urban areas.